Diagnosing Intraoperative Pneumothorax in Patients Undergoing Autologous Breast Reconstruction: A Useful Clinical Sign - Thomas Reekie; David McGill; Elizabeth Marshall (Case Reports in Surgery)
Intraoperative pneumothorax during breast reconstruction can be difficult to diagnose. Even a small pneumothorax can become a tension pneumothorax under positive pressure ventilation. The clinical finding of venous congestion in a pedicled latissimus dorsi flap, which could not be explained by problems with the vessels, preceded other signs of a tension pneumothorax in the case presented here. Given the difficulties of access to the chest by the anaesthetic team during breast procedures, this has the potential to be a useful adjunct in the diagnosis of this potentially serious intraoperative complication.